Producción de biodiésel por etanolisis utilizando aceites de fritura de hoteles y su uso en calderas pirotubulares (2015)
Biofuel production from waste cooking oil (WCO) is an important alternative for using in generating  biodiesel  also  it  helps  in  the  reuse  of  a  pollutant. This work seeks to determine the best performance of the production process of ethyl esters from the parameters: molar ratio WCO/ethanol (1: 5-1: 7), percentage of catalyst by weight (0.5 to 0.7%wt), reaction temperature (50-60 °C) and washing agent (40 °C Water - acetic acid)  using  the  transesterification  process  by  homogeneous  catalysis  alkaline  (NaOH).  The process was  carried  out  in  two  steps,  the  first stage  of  esterification   and other one transesterification with a reaction temperature of 60 °C, molar ratio WCO: ethanol 1: 7 and water as  washing  agent.  The biodiesel produced possesses physicochemical characteristics according to ASTM D6751 standard and 93.5% yield of ethylesters. The optimal conditions enable the use in biofuel “boiler” which functional diesel.